Nazistowski kolonializm prawny : (nie)porządek prawny Generalnego Gubernatorstwa (1939–1945) - Mielnik, Hubert (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article aims to provide a comprehensive description of the legal order of the General Government (1939–1945) and thus systemize the sources of the reconstruction of legal norms used in the processes of applying the law in the studied area. The analysis will be focused on issues related to jurisprudence and extra-legal axiologies to which the law in the General Government was subjected. The article is based on a comprehensive approach to the law of the General Government. It describes the creation of law in the GG (where it came from), the application of the law, and the factors that influenced this process. The presented characteristics provide the basis to describe the synthetic features of the GG’s legal order. It also argues that the German authorities deliberately created a politicized, colonial, uncertain, unclear, and racist legal order in the GG. Despite emerging from the sources of European civilization (including the legal one), the Nazi German legal order in the General Government was a contradiction of legalistic principles, guarantees, and values developed over the centuries. Therefore, the term “legal (dis)order” should be considered a proper definition of the described phenomenon. The article uses the research methods appropriate to jurisprudence and to interpreting historical sources.
Keywords: prawo nazistowskie; porządek prawny; system prawa; Generalne Gubernatorstwo; Trzecia Rzesza